PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 013 PEMATANG REBA KECAMATAN RENGAT BARAT - oktarina, Ria oktarina Ria; Alim, Jesi Alexander Alim Alexander; Alpusari, Mahmud Alpusari Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : This research aim to to increase result of learning mathematics clas student of III SD Negeri 013 Pametang Reba School year 2014 / 2015 research subjek class III SD Negeri 011 Pematang Reba with amount of student counted 30 student form this research of action class of PMRI with two cycle. Research data indicate that result learn natural student improvement, activity provision value learn cycle of I with mean 63,60. cycle of II mount with mean 84,71. student aktivita cycle of I with menat 59,71. cyle of II natural make-up of with mean 83,32. data result of natural research make-up of wher before conducted action with PMRI Indonesia realistic mathematics education complete elementary score only 8 people (26,66%) with mean 62,66. cycle of I mount completely reach 20 People (66,66%) with mean 72,16. and cycle of II mount completely reach 26 people (86,66 %) with mean 82,66. make-up of result learn in its entirety 31,91. Thereby can be concluded that hypothesis in this research “if applied model study of co-operative of tife make match a hence can improve result learn mathematics class student of III DN Negeri 013 Pematang Reba “ can be accepted.Keyword : mathematics Indonesia Realistic Mathematics education (PMRI). a result learn